Hubungan Nem, Pilihan Jurusan dan Nilai Tes Sipenmaru dengan Prestasi Belajar Mahasiswa JKL Yogyakarta - F.X. Amanto Rahardjo; Sri Puji Ganefati; Kapti Driantoto (Poltekkes Kemenkes Yogyakarta, 2008)
The objectives of the study were: to understand the number of applicants who chose Environmental Health Department (JKL) as their first choice, the ave-rage of applicants’ high school’s passing grade (NEM), and the average grade of their selection test. The study was aimed as well to reveal the relationship between those three factors with the Cummulative Achievement Index amongst JKL’s students. To attain its objectives, the study employed a cross sectional survey by collecting the corresponding data during the academic year between 2004/2005 and 2006/2007. The results showed a strong relationship between those three factors with the achievement of the students, of which the NEM was the biggest contributor. It was suggested that in the future the new student selection method could use the NEM selection only, since it is relatively more effective and efficient compared with conventional written test.